2005
DOI: 10.1080/02713680500346625
|View full text |Cite
|
Sign up to set email alerts
|

Mast Cell Chymase Decreases the Barrier Function and Inhibits the Migration of Corneal Epithelial Cells

Abstract: Human chymase causes the proteolysis of occludin and fibronectin, resulting in a decrease of barrier function and inhibition of the migration of corneal epithelial cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 60 publications
2
17
0
Order By: Relevance
“…Mast cell chymase has been shown to be apoptotic in leukemic T cells by inducing DNA fragmentation [32] as well as in vascular smooth muscle cells [33] and in keratinocytes [19]. In addition, chymase inhibited migration of corneal epithelial cells [34]. In our specimens, the lack of microsatellites might be explained by increased apoptosis and reduced migration of melanoma cells in the presence of chymase in the peritumoral stroma.…”
Section: Discussionmentioning
confidence: 78%
“…Mast cell chymase has been shown to be apoptotic in leukemic T cells by inducing DNA fragmentation [32] as well as in vascular smooth muscle cells [33] and in keratinocytes [19]. In addition, chymase inhibited migration of corneal epithelial cells [34]. In our specimens, the lack of microsatellites might be explained by increased apoptosis and reduced migration of melanoma cells in the presence of chymase in the peritumoral stroma.…”
Section: Discussionmentioning
confidence: 78%
“…Although the underlying mechanism has not been fully established, it has been suggested that mMCP-1 may promote inflammation by cleaving cell-cell contact proteins, such as occludin and ZO-1. 44,55,56 In line with such a notion, infusion of rats with rMCP-2, that is, a rat homolog of mMCP-1, causes increased epithelial permeability. 57 …”
Section: Parasite Infectionmentioning
confidence: 69%
“…44,55,56 Further, MC proteases may regulate the local gene expression pattern, as exemplified by the ability of tryptase to induce chemokine secretion. 34 It is also well known that tryptase can cleave and thereby activate protease-activated receptor 2, 85-87 a notion that is also supported by in vivo evidence.…”
Section: Effects On Cell Surface Proteinsmentioning
confidence: 99%
“…Consequently, mast cell chymase may affect barrier function through effects on any of these systems. Chymase directly alters corneal epithelial barrier function through proteolytic cleavage of fibronectin and the TJ protein occludin (30). Alternatively, mast cell/chymase may regulate epithelial barrier function indirectly via interactions with the enteric nervous system (ENS).…”
Section: Mcpt7 Andmentioning
confidence: 99%